Avaliação da apoptose e resposta Th17 em modelo murino de esporotricose - Ferreira, Lucas Souza [UNESP] (2014)
The discovery of T helper 17 (Th17) cells, along with many other Th cell subsets in the recent years, has expanded the Th1/Th2 paradigm that had persisted since its proposition by Mosmann and colleagues in 1986. Defined by the characteristic expression of the transcription factor retinoic acid receptor-related orphan receptor γt (RORγt) and production of interleukin (IL)-17, Th17 cells are powerful inducers of tissue inflammation with a recognized role against extracellular bacteria and fungi and in the maintenance of mucosal homeostasis. Despite all this, the interest in their study came from the pivotal role they play in the development of major chronic inflammatory conditions such as multiple sclerosis, rheumatoid arthritis and Crohn’s disease, reason why they have been the target of promising new therapies specifically aimed at their blockade. Accordingly, the identification of opportunistic pathogens whose clearance relies on the Th17 response is of huge prophylactic importance, for they could become a risk for patients subjected to anti-Th17 therapies. As shown here for the first time, this applies to Sporothrix schenckii, the agent of sporotrichosis, whose clinical importance was, until now, almost exclusively limited to immunodepressed individuals, either as a consequence of pharmacological treatment against transplant rejection or cancer, or due to various primary or acquired immunodeficiency disorders. In light of the above, the aim of this study was to assess the role of the Th17 response in the S. schenckii infection and its importance for the animal’s ability to eliminate the infection. In order to do that, we developed a murine model of S. schenckii systemic infection and assessed the development and effector cytokines production from Th17 cells. Additionally, the Th17 response’s importance for infection control was assessed by treating mice with an anti-IL-23p19 neutralizing monoclonal antibody, which was aimed at ...